Structure–Function Studies and Mechanism of Action of Snake Venom L-Amino Acid Oxidases - Ullah, Anwar (Frontiers in Pharmacology, 2020)
Snake venom L-amino acid oxidases (SV-LAAOs) are among the least studied in the venom enzymes. These enzymes catalyze the stereospecific oxidation of an L-amino acid to their corresponding α-keto acid with the liberation of hydrogen peroxide (H2O2) and ammonia (NH3). They display various pathological and physiological activities including induction of apoptosis, edema, platelet aggregation/inhibition, hemorrhagic, and anticoagulant activities. They also show antibacterial, antiviral and leishmanicidal activity. They have also been used as therapeutic agents in some disease conditions like cancer and anti-HIV drugs. Although the crystal structures of five SV-LAAOs are present in the Protein Data Bank (PDB), there is no single article that describes all of them. To better understand their structural properties and correlate it with their function, the current work describes structure characterization, structure-based mechanism of catalysis, inhibition and substrate specificity of SV-LAAOs. Sequence analysis indicates a high sequence identity (> 84%) among SV-LAAOs, comparatively a low sequence identity with Pig kidney D-amino acid oxidase (< 50%) and very low sequence identity (< 24%) with bacterial LAAOs, Fugal (L-lysine oxidase), and Zea mays Polyamine oxidase (PAAO). Their structure is composed three-domains, a FAD-binding domain, a substrate-binding domain and a helical domain. The sequence and structural analysis indicate that the amino acid residues in loops vary in length and composition due to which the surface charge distribution also vary in these enzymes that may impart variable substrate specificity to these enzymes. The active site cavity volume and its average depth also vary in these enzymes. The inhibition of these enzymes by synthetic inhibitors will lead to the production of more potent antivenoms against snakebite envenomation.